Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kreatif Siswa Kelas IV pada Materi Gaya dan Gerak - Sri Rahayu; Irwan Koto (UNIB Press, 2023)
This research is a quantitative research with a quasy experiment method. The research design was The Matching Only Pretest-Posttest Control Group Design. The sampling technique used purposive sampling. The population in this study were fourth grade students at SD Negeri 02 Rejang Lebong and grade IV students at SD Negeri 10 Rejang Lebong. The samples of this research were 30 students of class IV A SDN 02 Rejang Lebong as the experimental class and 30 students of class IV A SDN 10 Rejang Lebong as the control class. The research instrument is a written test which includes tests of fluency, flexibility, original thinking skills, elaboration of thinking skills and evaluation thinking skills. Significance level of 0.05. Based on the results of the posttest hypothesis test for the experimental and control classes using the Mann-Whitney U test, it was found that there was a difference in the effect of using different learning models on the dimensions of creative thinking abilities. Statistically, N-Gain the average value of the dimensions of creative thinking skills using PBL is much higher than learning using conventional models. Hypothesis test pretest-posttest experimental class using Paired Samples Test all dimensions of creative thinking ability obtained value t-count < t-table. It is concluded that there is an effect of the application of the PBL model on the creative thinking ability of class IV in the material of energy and motion.